USING ACCOUNTING INFORMATION FOR STRATEGIC DECISION-MAKING IN A MULTI-SEGMENTED COMPANY - Mihaylova, Lyudmila; Papazov, Emil (Copernican Journal of Finance & Accounting, 2018)
The reason of being of corporate accounting is not only to record, interpret and present data about existing business processes, but also to provide information for supporting main decision-making activities of management. This article presents basic problems outlining the relationship between accounting and strategic management of companies. The main ideas are connected with the philosophy of presenting information in financial and management reports, on the one hand, and the levels of management activities and their relationship to the development strategy of the organization, on the other hand. The aim is to trace the relationship between the segmental accounting and the strategic management of diversified organizations and to highlight problem areas, deserving management attention. The research methods of analysis and synthesis have been used. The outcomes of the research show that choosing a proper cost structure and allocation basis at operating segment level will contribute to increasing the capabilities of managers to make better corporate strategic decisions.